2014
DOI: 10.1007/s00128-014-1416-1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Geochemical and Environmental Factors on Seasonal Variation of Heavy Metals in a Coastal Lagoon Yucatan, Mexico

Abstract: This study investigated the influence of geochemical and environmental factors on seasonal variation in metals in Yucatan's Chelem lagoon. Anthropogenic activities discharge non-treated wastewater directly into it with detrimental environmental consequences. Accordingly, this study established the spatial and temporal patterns of fine grain sediments and concentrations of heavy metals. Multivariate analyses showed fine grain facies deposition, transition sites dominated by fine grain transport, and fine grain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 18 publications
(30 reference statements)
0
16
0
Order By: Relevance
“…The effects of these sedimentary dynamics on the diversity and community structure of the macrofauna have not been evaluated in this region, but it has been demonstrated in other latitudes (Walker et al, 2008;Schlacher et al, 2012;Munari, 2013). In addition, there are other sources of pollution related to the karstic characteristics of the Yucatan Peninsula, that allow pollutants generated by activities carried out inland to permeate, flow and enter to the coast by submerged groundwater discharges; some evidence of that is the presence of human fecal material (coprostanol and epicoprostanol) in sediments surrounding the springs located in Dzilam de Bravo (Kantun-Manzano et al, 2018), as well as the results reported by Arcega-Cabrera et al (2015) concerning heavy metal pollution in Chelem Lagoon connected to inland anthropogenic activities along with local factors.…”
Section: Pollutants Patternsmentioning
confidence: 73%
“…The effects of these sedimentary dynamics on the diversity and community structure of the macrofauna have not been evaluated in this region, but it has been demonstrated in other latitudes (Walker et al, 2008;Schlacher et al, 2012;Munari, 2013). In addition, there are other sources of pollution related to the karstic characteristics of the Yucatan Peninsula, that allow pollutants generated by activities carried out inland to permeate, flow and enter to the coast by submerged groundwater discharges; some evidence of that is the presence of human fecal material (coprostanol and epicoprostanol) in sediments surrounding the springs located in Dzilam de Bravo (Kantun-Manzano et al, 2018), as well as the results reported by Arcega-Cabrera et al (2015) concerning heavy metal pollution in Chelem Lagoon connected to inland anthropogenic activities along with local factors.…”
Section: Pollutants Patternsmentioning
confidence: 73%
“…Arcega-Cabrera et al [35] evaluated seasonal variations and the natural and environmental factors that influence the concentrations of heavy metals in the Chelem Lagoon, Yucatán; metals were measured by AAS in samples collected during the dry, rainy, and post-rainy seasons. Cd, Cu, Cr, and Pb concentrations presented statistically significant spatial and temporal variations, and concentrations of Pb, As, Cd, and Zn were found to be above sediment quality standards.…”
Section: Sediments In Lakes Lagoons and Damsmentioning
confidence: 99%
“…Groundwater contributes the majority of urban and agricultural water in Mexico (INEGI 2015) and long-term monitoring of aquifers, including more recent satellite-based measurements, indicates moderate to severe conditions of groundwater overuse (Castellazzi et al 2016). Groundwater contamination caused by deficient waste water treatment and lack of correct solid-waste disposal is also an increasing problem in Mexico, where rapid economic and demographic growth has promoted accelerated environmental degradation (Arcega-Cabrera et al 2014a, 2014b, 2017, 2018Camacho-Cruz et al 2019). Sustainable use of existing groundwater supplies, along with protection of groundwater from human-made pollutants is essential for water security in Mexico.…”
Section: Introductionmentioning
confidence: 99%